2016
DOI: 10.21037/atm.2016.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Plasma alkaline phosphatase and survival in diabetic patients with acute myocardial infarction

Abstract: Background: Alkaline phosphatase (ALP) removes phosphate groups from many types of molecules. The aim of the present research was to study the relation between plasma ALP and survival in diabetic patients with myocardial infarction.Methods: Retrospective study: from 954 admissions (15 months period) in a coronary care unit, we selected 200 admissions corresponding to 195 patients with myocardial infarction and diabetes mellitus. Survival after no less than 48 months, and up to 61 months, after the myocardial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Alkaline phosphatase (ALP) is a generally accepted clinical marker of hepatic or bone disease [ 7 ]. It had been showed that elevated ALP acted as a prognostic indicator of decreased survival in diabetic patients with acute myocardial infarction (MI), possibly in association to decreased renal function in male patients [ 8 ]. At the same time, the combined effect of vascular calcification (VC) and higher ALP was associated with a greater risk of cardiovascular events and death, and high serum ALP increased the risk associated with VC in end-stage kidney disease patients starting dialysis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is a generally accepted clinical marker of hepatic or bone disease [ 7 ]. It had been showed that elevated ALP acted as a prognostic indicator of decreased survival in diabetic patients with acute myocardial infarction (MI), possibly in association to decreased renal function in male patients [ 8 ]. At the same time, the combined effect of vascular calcification (VC) and higher ALP was associated with a greater risk of cardiovascular events and death, and high serum ALP increased the risk associated with VC in end-stage kidney disease patients starting dialysis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, we retrospectively studied data concerning a cohort of diabetic patients with myocardial infarction. 1 , 2 , 3 We now studied the relation between ECG data at admission and survival. Particular attention was paid to the PR interval, since conflicting data exist in the literature concerning the prognostic significance of a prolonged PR interval.…”
mentioning
confidence: 99%
“…The present study was retrospective and part of the methods have been described in the previous reports. 1 , 2 The survival of patients was established by the study of electronic health records.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by the survival curves for 48 months of follow-up, patients with ALP >74 IU/L had approximately 60% survival compared with 80% in the group with ALP <74 IU/L. 59 In a prospective study involving 1636 patients, where ALP was tested as a biomarker for the survival of patients with MI, a linear correlation was seen between ALP concentrations and mortality in these patients. Moreover, regarding the outcome of pPCI, higher ALP concentrations accurately predicted stent thrombosis as well as the risk of repeat MI.…”
Section: Alkaline Phosphatasementioning
confidence: 97%